Teaching physical education for learning - Rink, Judith E.
Teaching physical education for learning, eighth edition focuses on the instructional skills teachers need to be effective in producing student learning. This text provides students who are working to become physical education teachers with the understanding that learning to be a teacher begins with understanding teaching as a process of selecting goals and designing educational experiences consistent with how students learn to help students achieve those goals. Focusing on physical education from kindergarten through grade 12, this user-friendly text emphasizes teaching strategies and theories to give future teachers a foundation for designing effective learning experiences